2018
DOI: 10.1371/journal.pone.0207982
|View full text |Cite|
|
Sign up to set email alerts
|

A deep learning model for the detection of both advanced and early glaucoma using fundus photography

Abstract: PurposeTo build a deep learning model to diagnose glaucoma using fundus photography.DesignCross sectional case study Subjects, Participants and Controls: A total of 1,542 photos (786 normal controls, 467 advanced glaucoma and 289 early glaucoma patients) were obtained by fundus photography.MethodThe whole dataset of 1,542 images were split into 754 training, 324 validation and 464 test datasets. These datasets were used to construct simple logistic classification and convolutional neural network using Tensorfl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
110
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(112 citation statements)
references
References 14 publications
1
110
0
1
Order By: Relevance
“…The merits of transfer learning in the field of automated glaucoma detection using fundus images have been illustrated using both small (Ahn et al. ; Shibata et al. ) and large (Christopher et al.…”
Section: Discussionmentioning
confidence: 99%
“…The merits of transfer learning in the field of automated glaucoma detection using fundus images have been illustrated using both small (Ahn et al. ; Shibata et al. ) and large (Christopher et al.…”
Section: Discussionmentioning
confidence: 99%
“…Email address: gwenole.quellec@inserm.fr (Gwenolé Quellec) 2019; Ahn et al, 2019;Diaz-Pinto et al, 2019) and age-related macular degeneration (AMD) (Matsuba et al, 2018;Pead et al, 2019), the other two major sight-threatening pathologies in developed countries. Other pathologies such as retinopathy of prematurity (Wang et al, 2018) have also been targeted.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there is a need for development of automatic methods for GON detection based on fundus images. Several reports have proved the efficacy of machine learning in glaucoma [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies of DR using deep machine learning showed high sensitivity and specificity for the detection of changes typical for DR [11,12,15]. The detection of glaucoma may be more challenging than the diagnosis of DR because it relies on estimation of subtle changes in the ONH shape and cupping including the stage of glaucoma and refractive errors of the eye [9,14].…”
Section: Introductionmentioning
confidence: 99%